1951
DOI: 10.1099/00221287-5-4-714
|View full text |Cite
|
Sign up to set email alerts
|

On the Nutrition of Desulphovibrio desulphuricans

Abstract: SUMMARY: A liquid medium based on peptone, yeast extract and glucose is described, which is capable of supporting massive growth of Desulphovibrio desulphuricuns 'Hildenborough' and certain other strains of sulphate-reducing bacteria. When peptone is used in large amounts yeast extract may be omitted, though yeast extract is stimulatory when the peptone supply is suboptimal. Glucose is better than lactate in this medium. Bicarbonate increases the growth rate. More than one factor is responsible for growth stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1953
1953
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Cytochromes were eluted with starting buffer. After washing with 1 1 10 mM Tris/Cl, pH 8.0, plus 20 mM NaCl, a 20-400 mM NaCl gradient in 10 mM Tris/Cl, pH 8.0, (2 1) was applied to separate the bound proteins into two main fractions: a brownish fraction (60-110 mM NaCl) with the prismane protein (see below), (partially inactivated) periplasmic hydrogenase, adenosine-5'-phosphosulfate (APS) reductase, assimilatory sulfite reductase and a greenish-brown fraction containing desulfoviridin and ferredoxin. The brownish fraction (typically 400 ml) was concentrated using an Amicon device with YM-30 filter.…”
Section: Growth and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochromes were eluted with starting buffer. After washing with 1 1 10 mM Tris/Cl, pH 8.0, plus 20 mM NaCl, a 20-400 mM NaCl gradient in 10 mM Tris/Cl, pH 8.0, (2 1) was applied to separate the bound proteins into two main fractions: a brownish fraction (60-110 mM NaCl) with the prismane protein (see below), (partially inactivated) periplasmic hydrogenase, adenosine-5'-phosphosulfate (APS) reductase, assimilatory sulfite reductase and a greenish-brown fraction containing desulfoviridin and ferredoxin. The brownish fraction (typically 400 ml) was concentrated using an Amicon device with YM-30 filter.…”
Section: Growth and Isolationmentioning
confidence: 99%
“…Desuljovihrio vulgaris (Hildenborough) NCIB 8303 was maintained on Postgate's medium [20]. For localization experiments of Desulfovibrio strains, cells were grown in Saunders' N medium [21] to an absorbance of approximately 0.8 at 660 nm.…”
Section: Growth and Isolationmentioning
confidence: 99%
“…They reduced sulphate, produced desulfoviridin, and were progressively motile vibrios. Although, in nitrogen-fixation experiments, the sulphate-reducing vibrios were the predominant organisms in these isolates, microscopic examination revealed some contaminating bacteria, confirmed by growth on the medium described by Postgate (1951). In older cultures it was sometimes dificult to detect microscopically anything but Desulfovibrio forms ; however, transfer of the culture into fresh medium containing combined nitrogen encouraged growth of the contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfate reducer D. vulgaris (Hildenborough) NCIB 8303 was maintained on Postgate's medium [14] ; large-scale growth at 35 "C on lactate/sulfate was in modified Saunders' medium [15]. Stirred batch cultures of 240 1 were grown under nitrogen to an A,,, value of approximately 0.8 in 60 h from a 1 % inoculum in a home-built anaerobic glass fermentor.…”
Section: Organism Growth and Isolationmentioning
confidence: 99%
“…Subsequently, however, the structural gene for Hmc was sequenced by Pollock et al, who found 16 regions encoding Cys-Xaa-Xaa-Cys-His motifs for the potential covalent binding of 16 hemes [4]. Furthermore, with this gene transferred to Desulfovibrio desulfuricans, strain G200, an overexpression system was constructed and the purified recombinant Hmc contained [13][14][15][16] hemes by chemical analysis [lo].…”
mentioning
confidence: 99%